Streptococcus uberis strains isolated from the bovine mammary gland evade immune recognition by mammary epithelial cells, but not of macrophages - Günther, Juliane; Czabanska, Anna; Bauer, Isabel; Leigh, James A.; Holst, Otto; Seyfert, Hans-Martin (BioMed Central, 2016)
Streptococcus uberis is frequently isolated from the mammary gland of dairy cattle. Infection with some strains can induce mild subclinical inflammation whilst others induce severe inflammation and clinical mastitis. We compared here the inflammatory response of primary cultures of bovine mammary epithelial cells (pbMEC) towards S. uberis strains collected from clinical or subclinical cases (seven strains each) of mastitis with the strong response elicited by Escherichia coli. Neither heat inactivated nor live S. uberis induced the expression of 10 key immune genes (including TNF, IL1B, IL6). The widely used virulent strain 0140J and the avirulent strain, EF20 elicited similar responses; as did mutants defective in capsule (hasA) or biofilm formation (sub0538 and sub0539). Streptococcus uberis failed to activate NF-κB in pbMEC or TLR2 in HEK293 cells, indicating that S. uberis particles did not induce any TLR-signaling in MEC. However, preparations of lipoteichoic acid (LTA) from two strains strongly induced immune gene expression and activated NF-κB in pbMEC, without the involvement of TLR2. The immune-stimulatory LTA must be arranged in the intact S. uberis such that it is unrecognizable by the relevant pathogen receptors of the MEC. The absence of immune recognition is specific for MEC, since the same S. uberis preparations strongly induced immune gene expression and NF-κB activity in the murine macrophage model cell RAW264.7. Hence, the sluggish immune response of MEC and not of professional immune cells to this pathogen may aid establishment of the often encountered belated and subclinical phenotype of S. uberis mastitis.